2022
DOI: 10.3390/ani12141795
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Effect of Oxytocin Use in Farrowing Sows on Stillbirth Rate: A Systematic Review with a Meta-Analysis

Abstract: The objective of this systematic review and meta-analysis was to identify the benefits and possible adverse side effects of oxytocin use during farrowing. Randomized controlled trials that were published in English within the last 50 years were eligible for inclusion. Eligible research needed to contain the PICO elements: population (P)—sows at farrowing; intervention (I):—oxytocin given to sows—comparator (C): sows at farrowing not given oxytocin, as well as sows given different dosages and/or different timin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(237 reference statements)
0
1
0
Order By: Relevance
“…Reducing farrowing duration involves several approaches. Although uterotonics (e.g., oxytocin or its analogs) can reduce farrowing duration, administration in the early process increases the stillbirth rate [61,91,92]. Recently, it has been shown that carbetocin is also associated with reduced colostrum yield [91,93].…”
Section: Strategies and Tools To Optimize Performance At Farrowingmentioning
confidence: 99%
“…Reducing farrowing duration involves several approaches. Although uterotonics (e.g., oxytocin or its analogs) can reduce farrowing duration, administration in the early process increases the stillbirth rate [61,91,92]. Recently, it has been shown that carbetocin is also associated with reduced colostrum yield [91,93].…”
Section: Strategies and Tools To Optimize Performance At Farrowingmentioning
confidence: 99%